1) "\\lim\\limits_{|x|\\to+\\infty}x^u\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(\\frac{\\partial^{|\\alpha|}\\varphi}{\\partial x^\\alpha}\\bigr)=\\lim\\limits_{|x|\\to+\\infty}x^u\\frac{\\partial^{|\\alpha+\\beta|}\\varphi}{\\partial x^{\\alpha+\\beta}}". Since "\\varphi\\in S", we have "\\lim\\limits_{|x|\\to+\\infty}x^u\\frac{\\partial^{|\\alpha+\\beta|}\\varphi}{\\partial x^{\\alpha+\\beta}}=0", so "\\frac{\\partial^{|\\alpha|}\\varphi}{\\partial x^\\alpha}\\in S"
2)Prove by induction on "|\\beta|" that "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=\\sum\\limits_{\\gamma\\le\\inf\\{\\alpha,\\beta\\}}\\sum\\limits_{\\delta\\le\\beta}C_{\\gamma\\delta}x^{\\alpha-\\gamma}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}" for some "C_{\\gamma\\delta}" (if "\\varepsilon" and "\\rho" are multiindices, then "\\varepsilon\\le\\rho\\Leftrightarrow\\forall i=1,\\ldots,n\\ \\varepsilon(i)\\le\\rho(i)" ).
a)If "|\\beta|=0", then "\\gamma=0" and "\\delta=0", so "C_{00}=1"
b)Let it is true for all "|\\beta|", where "|\\beta|\\le k".
c)Consider "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)", where "|\\beta|=k+1". Then "\\beta(s)=\\begin{cases}\n\\beta'(s),&\\text{if $s\\neq t$}\\\\\n\\beta'(s)+1,&\\text{if $s=t$}\n\\end{cases}" for some "t" and "\\beta'", where "|\\beta'|=k".
So "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=\\frac{\\partial}{\\partial x_t}\\left(\\frac{\\partial^{|\\beta'|}}{\\partial x^{\\beta'}}\\bigl(x^\\alpha\\varphi\\bigr)\\right)" . By induction hypothesis we have "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=\\frac{\\partial}{\\partial x_t}\\left(\\sum\\limits_{\\gamma'\\le\\inf\\{\\alpha,\\beta'\\}}\\sum\\limits_{\\delta'\\le\\beta'}C_{\\gamma'\\delta'}x^{\\alpha-\\gamma'}\\frac{\\partial^{|\\delta'|}\\varphi}{\\partial x^{\\delta'}}\\right)="
"\\sum\\limits_{\\gamma'\\le\\inf\\{\\alpha,\\beta'\\}}\\sum\\limits_{\\delta'\\le\\beta'}C_{\\gamma'\\delta'}\\left(\\frac{\\partial x^{\\alpha-\\gamma'}}{\\partial x_t}\\frac{\\partial^{|\\delta'|}\\varphi}{\\partial x^{\\delta'}}+x^{\\alpha-\\gamma'}\\frac{\\partial^{|\\delta'+1|}\\varphi}{\\partial x^{\\delta'}\\partial x_t}\\right)"
Let "\\gamma(s)=\\begin{cases}\n\\gamma'(s),&\\text{if $s\\neq t$}\\\\\n\\gamma'(s)+1,&\\text{if $s=t$}\n\\end{cases}" and "\\delta(s)=\\begin{cases}\n\\delta'(s),&\\text{if $s\\neq t$}\\\\\n\\delta'(s)+1,&\\text{if $s=t$}\n\\end{cases}" , then "\\gamma\\le\\beta" and "\\delta\\le\\beta"
We have "\\frac{\\partial x^{\\alpha-\\gamma'}}{\\partial x_t}=\\begin{cases}\n(\\alpha(t)-\\gamma'(t))x^{\\alpha-\\gamma},&\\text{if $\\gamma\\le\\alpha$}\\\\\n0,&\\text{if $\\gamma\\le\\alpha$ is false}\n\\end{cases}" , so "\\frac{\\partial x^{\\alpha-\\gamma'}}{\\partial x_t}\\frac{\\partial^{|\\delta'|}\\varphi}{\\partial x^{\\delta'}}=0" if "\\gamma\\le\\alpha" is false, and "\\frac{\\partial x^{\\alpha-\\gamma'}}{\\partial x_t}\\frac{\\partial^{|\\delta'|}\\varphi}{\\partial x^{\\delta'}}=(\\alpha(t)-\\gamma(t))\\frac{\\partial x^{\\alpha-\\gamma}}{\\partial x_t}\\frac{\\partial^{|\\delta'|}\\varphi}{\\partial x^{\\delta'}}" if "\\gamma\\le\\alpha" . Also we have "\\gamma\\le\\beta" and "\\delta'\\le\\delta\\le\\beta".
Next, "x^{\\alpha-\\gamma'}\\frac{\\partial^{|\\delta'+1|}\\varphi}{\\partial x^{\\delta'}\\partial x_t}=x^{\\alpha-\\gamma'}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^{\\delta}}" , where "\\gamma'\\le\\gamma\\le\\beta", "\\gamma'\\le\\alpha" and "\\delta\\le\\beta" .
So we obtain that "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)" is linear combination of "x^{\\alpha-\\gamma}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}" , where "\\gamma\\le\\inf\\{\\alpha,\\beta\\}" and "\\delta\\le\\beta".
By principle of mathematical induction we have that "\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=\\sum\\limits_{\\gamma\\le\\inf\\{\\alpha,\\beta\\}}\\sum\\limits_{\\delta\\le\\beta}C_{\\gamma\\delta}x^{\\alpha-\\gamma}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}" for some "C_{\\gamma\\delta}" .
Then "\\lim\\limits_{|x|\\to+\\infty}x^u\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=\\lim\\limits_{|x|\\to+\\infty}x^u\\sum\\limits_{\\gamma\\le\\inf\\{\\alpha,\\beta\\}}\\sum\\limits_{\\delta\\le\\beta}C_{\\gamma\\delta}x^{\\alpha-\\gamma}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}="
"=\\sum\\limits_{\\gamma\\le\\inf\\{\\alpha,\\beta\\}}\\sum\\limits_{\\delta\\le\\beta}C_{\\gamma\\delta}\\lim\\limits_{|x|\\to+\\infty}x^{\\alpha-\\gamma+u}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}"
Since "\\varphi\\in S", for every "\\gamma" and "\\delta" from sum we have "\\lim\\limits_{|x|\\to+\\infty}x^{\\alpha-\\gamma+u}\\frac{\\partial^{|\\delta|}\\varphi}{\\partial x^\\delta}=0", so "\\lim\\limits_{|x|\\to+\\infty}x^u\\frac{\\partial^{|\\beta|}}{\\partial x^\\beta}\\bigl(x^\\alpha\\varphi\\bigr)=0". That is "x^\\alpha\\varphi\\in S".
Comments
Leave a comment